Utilization of horseradish tree (Malunggay) leaves in pasta - Chiu, Patricia F.K.; Dumelod, Benelyn Domingo (1994., 1994)
There is a need to encourage people to increase their intake of vitamin A-rich foods due to the serious deficiency problem in the country. It was for this purpose that three levels of malunggay leaves--16%, 20%, and 24%-- were incorporated into pasta. These levels were determined in view of the objective which is the maximal incorporation of malunggay leaves into pasta without significantly affecting the sensory and cooking qualities of the product. In Phase 1, the three levels of incorporation and three trials of production showed no significant differences in production data, physical test results, sensory attributes, and acceptability. It was for this reason and also for purposes of nutrition and economy, that the 24% level of incorporation was selected for bench-scale production in Phase 2. When compared with the pasta of the selected level of malunggay incorporation, the pasta from the bench-scale production had higher drying and production yields, similar water absorption capacity, but poorer cooking quality. There was no significant differences between the mean sensory scores of pasta from both phases. Protein content of the cooked malunggay pasta was 8% per serving portion (100 g), meeting 13% and 15%, respectively, of the RDA for adult Filipino males and females. Vitamin A content was 633 μg RE/100g, which was 121% of the Philippine RDA for males and 141% for females. The unit cost of the pasta (250 g) was calculated to be P81.44. Mark-up of this cost by 10% resulted to a price thrice that of commercial spinach pasta. High overhead costs were incurred due to the use of production facilities that were not suited for large-scale production. To improve cooking quality, recommendations included the partial replacement of all-purpose flour with semolina or the use of dried, powdered malunggay leaves, instead of fresh leaves for incorporation into the pasta. However, the effect of these ingredients on the cost of production should also be considered. The use of large-scale production facilities were also recommended to cut overhead costs. Determination of the chemical score of the pasta could be done to assess protein quality. Further studies concerning the kinetics of vitamin A loss in storage and improvement of packaging material could be done.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Horse-radish.